Etika Komunikasi sebagai Pendorong Pembangunan Masyarakat Desa - Rizka Pratiwi Pramono; Abdur Rahman Rahim Marbun; Febriani Syahputri Maha (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2023)
This research aims to describe community participation in village community development, as well as determine the driving factors that influence active community participation in village community development. The method used in this research is literature study, which is taken from several journals related to the material discussed in this journal. The result of this research is that the success of a development process cannot be separated from the participation of members of the community, because in principle development is shown to create a prosperous society. Therefore, the responsibility for the success or failure of development is not only in the hands of the government but also in the hands of the community. Therefore, awareness and active participation from the community is one of the keys to successful development, in this case achieving development targets needs to be demonstrated by government policy. In this connection it can be said that development which is in process is determined by the size of community participation, namely participation in planning, participation in implementation, participation in monitoring and assessment.